Preparation of low-dimensional carbon material-based metal nanocomposites using a polarizable organic/water interface. Issue 18 (4th September 2015) - Toth, Peter S.; Haigh, Sarah J.; Rabiu, Aminu K.; Rodgers, Andrew N.J.; Rakowski, Alexander M.; Dryfe, Robert A.W.
Abstract: Abstract : Single wall carbon nanotubes (SWCNTs) and liquid-phase exfoliated multilayer graphene (MLG) material thin films were assembled at a polarizable organic/water interface. A simple, spontaneous route to functionalize/decorate the interfacial assembly of MLG and SWCNTs with noble metal nanoparticles, at the interface between two immiscible electrolyte solutions (ITIES), is reported. The formation of MLG- or SWCNT-based metal nanocomposites was confirmed using various microscopic (scanning electron, transmission electron, and atomic force microscopy) and several spectroscopic (energy dispersive x-ray and Raman spectroscopy) techniques. Increasing the interfacial deposition time of the metal nanoparticles on the assembled low-dimensional carbon material increased the amount of the metal particles/structures, resulting in greater coverage of the MLG or SWCNTs with metal nanoparticles. This low-cost and convenient solution chemistry based impregnation method can serve as a means to prepare nanoscale carbonaceous material-based metal nanocomposites for their potential exploitation as electro-active materials, e.g., new generation catalysts or electrode materials.